A plastic-damage model for concrete in fire: Applications in structural fire engineering - Gernay, Thomas; Franssen, Jean-Marc (Fire safety journal, 2015)
The research aims at developing a new multiaxial constitutive model for concrete in the fire situation. In addition to validity at the material level, a crucial feature of a constitutive model is the applicability at the structural level; yet for concrete in fire there remains a serious lack of models combining reliability and robustness. The theoretical aspects and validation of the new model, which rely on a plastic-damage formulation, have been the subject of a former publication; they are briefly summarized here. This paper explores the capabilities of the concrete model for being used in a performance-based structural fire engineering framework. Several examples of numerical simulations by non-linear finite element method are discussed, with emphasis on practical applications that are demanding for the material model. In particular, it is shown that the simulations using the new concrete model succeed in capturing, at ambient temperature, the crack pattern in a plain concrete specimen and the influence of the loading path on reinforced concrete (RC) slabs. At high temperature, the presented applications include a RC slab subjected to furnace fire and a large-scale composite steel–concrete structure subjected to natural fire. In the numerical analyses, no parameter calibration was required on the particular concrete type, except for the uniaxial strengths and tensile crack energy which are to be defined case-by-case. The results illustrate the reliability and numerical robustness of the model. Also, they suggest that satisfactory prediction of structural behavior in fire can be obtained when no additional data is available on the specific properties of the particular concrete mix that is used in the project, as is often the case in practice, by using standard values of parameters. •A constitutive model has been developed for concrete at high temperature.•The model includes plasticity, damage and transient creep components.•The model is used in advanced numerical analyses of concrete structures in fire.•Standard values are used for the parameters of the model (no calibration required).•The results illustrate the applicability and robustness of the concrete model.